2020
DOI: 10.3390/ijms21176311
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Limit Ear Swelling Independently of the Chymase Mouse Mast Cell Protease 4 in an MC903-Induced Atopic Dermatitis-Like Mouse Model

Abstract: Atopic dermatitis (AD) is a complex, often lifelong allergic disease with severe pruritus affecting around 10% of both humans and dogs. To investigate the role of mast cells (MCs) and MC-specific proteases on the immunopathogenesis of AD, a vitamin D3-analog (MC903) was used to induce clinical AD-like symptoms in c-kit-dependent MC-deficient Wsh−/− and the MC protease-deficient mMCP-4−/−, mMCP-6−/−, and CPA3−/− mouse strains. MC903-treatment on the ear lobe increased clinical scores and ear-thickening, along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Since the ratio of activated T cells to Tregs in the skin was significantly higher in Kit W-sh/W-sh mice reconstituted with Il2 -/- MCs than in those reconstituted with WT MCs, it was concluded that MCs inhibit dermatitis by maintaining Tregs via IL-2 production ( 19 ). Exacerbated phenotypes in Kit W-sh/W-sh mice have also been reported in the MC903-induced AD model ( 36 ), but the underlying mechanisms by which MCs suppress inflammation in this model remain unclear.…”
Section: Atopic Dermatitismentioning
confidence: 96%
“…Since the ratio of activated T cells to Tregs in the skin was significantly higher in Kit W-sh/W-sh mice reconstituted with Il2 -/- MCs than in those reconstituted with WT MCs, it was concluded that MCs inhibit dermatitis by maintaining Tregs via IL-2 production ( 19 ). Exacerbated phenotypes in Kit W-sh/W-sh mice have also been reported in the MC903-induced AD model ( 36 ), but the underlying mechanisms by which MCs suppress inflammation in this model remain unclear.…”
Section: Atopic Dermatitismentioning
confidence: 96%
“…As an alarmin cytokine, IL-33 is crucial for the development of skin diseases. , Studies using the conditional knockout of St2 in sensory neurons have revealed that sensory-neuron-restricted ST2 signaling is a critical regulator of itch in dry skin mice . Moreover, IL-33 has been shown to be upregulated in the inflamed skin and regulate chronic itch in MC903-induced AD-like mice and urushiol-challenged ACD itchy mice. , …”
Section: Central Glial Cells and Itchmentioning
confidence: 99%
“…MC903-induced dermatitis was dependent on thymic stromal lymphopoietin (TSLP), IL-25 and IL-33 in BALB/c mice ( 76 ), and on TSLP, but not IL-25 or IL-33, in C57BL/6 mice ( 77 ). Mast cells were involved in TSLP production and induction of skin inflammation in MC903-induced dermatitis ( 78 ).…”
Section: Mast Cells In Atopic Dermatitismentioning
confidence: 99%